(untitled) (Journal of Economic Research & Business Administration, 2016)
This article describes the organization of management accounting in the processing of milk, including problems related to protsesa control equipment, preparation, production, sale. Accounting in modern conditions of formation of the market does not provide the function of providing information system in the milk processing companies at that level, which is necessary in making operational decisions, which requires a mechanism of formation of management accounting. The very concept of management accounting has not been fully applied in the organizations or companies processing of off milk in our country yet. For this reason it is necessary to improve system of accounting, to develop a technique of management accounting on «fields of activity» is a supply preparation, production processing,sale realization and management of this field of activity. This article not only enhances importance of costs management as increasing organization’s efficiency tool and also proposes marginal analysis methods.